2013
DOI: 10.7860/jcdr/2013/5617.2990
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Colour Doppler Ultrasonography in the Diagnosis of Fascial Space Infections - A Cross Sectional Study

Abstract: Aims and Objectives: (1) To evaluate the role of ultrasonography with colour Doppler in the diagnosis of fascial space infections, (2) To determine the nature, size and extent of the odontogenic infections which involve the primary and secondary fascial spaces of the maxilla and the mandible (3) To evaluate the sensitivity of ultrasonography in determining whether the inflammatory process is in a stage of cellulitis or abscess and to thus determine the appropriate time for a surgical intervention during the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Generally, it is recommended to remove the infection source (usually the causative tooth) during incision and drainage, if the patient's condition allows it [ 6 , 15 , 16 ]. Early diagnosis and appropriate treatment are crucial for quick recovery, shortening the hospitalization period, and reducing the risk of severe systemic complications [ 5 , 9 , 17 , 18 ]. Systemic treatment includes empirical antibiotic therapy according to the antibiogram.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is recommended to remove the infection source (usually the causative tooth) during incision and drainage, if the patient's condition allows it [ 6 , 15 , 16 ]. Early diagnosis and appropriate treatment are crucial for quick recovery, shortening the hospitalization period, and reducing the risk of severe systemic complications [ 5 , 9 , 17 , 18 ]. Systemic treatment includes empirical antibiotic therapy according to the antibiogram.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Douglas et al [13] found a 65 % sensitivity for the examination. Along this same line of research, Pallagatti et al [14] and Nisha et al [12] respectively determined an accuracy of 88.9 and 97.1 % for US. According to some authors, US is a complementary examination that helps confirm the diagnosis of abscesses and delineate their anatomic location, differentiating them from of cellulitis [11,15], and thereby demonstrating the presence of fluids or abscesses in the superficial spaces of the face [3] distinguishing the stage of the infection [16].…”
Section: Discussionmentioning
confidence: 79%
“…This percentage is in contrast to that obtained by various authors who analyzed nonspecific swelling in orofacial soft tissues. They evaluated lesions of probable inflammatory nature and found a sensitivity of 96 %, that is, the fraction of the patients who showed a positive response in the ultrasonographic examination among those individuals who had the disease [8][9][10][11][12]. On the contrary, Douglas et al [13] found a 65 % sensitivity for the examination.…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnosis of soft tissue lesions, several imaging methods such as CT, MRI, and USG can be used 9 . However the disadvantages of CT include ionizing radiation, high costs, technical sensitivity, inability to differentiate the soft tissues and some kind of artifacts 13 . Although MRI provides excellent soft tissue contrast resolution without ionizing radiation, the disadvantages of this method are the high costs, longer scan time, and the fact that it is not suitable for every patient 9 .…”
Section: Discussionmentioning
confidence: 99%
“…USG is a non-ionizing, rapid, non-invasive, widely available and cost-effective imaging technique used in medical diagnostics and intraoperative guidance in several fields of medicine 13 . It transmits high-frequency sound waves into the region of interest.…”
Section: Discussionmentioning
confidence: 99%